2008
DOI: 10.1177/019027250807100207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Diagnosis in the Modified Labeling Theory of Mental Illness

Abstract: Numerous studies over the past two decades suggest that when individuals are diagnosed with a mental illness,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…In regard to self-stigma, it is suggested that cultural ideas and stereotypes linked with mental illness and the mentally ill become personally relevant and promote negative selfimage perceptions (Kroska and Harkness 2008). To avoid such negative perceptions, it appears that students typically resist seeking help for problems that are socially and culturally stigmatised.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to self-stigma, it is suggested that cultural ideas and stereotypes linked with mental illness and the mentally ill become personally relevant and promote negative selfimage perceptions (Kroska and Harkness 2008). To avoid such negative perceptions, it appears that students typically resist seeking help for problems that are socially and culturally stigmatised.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Holmes and River (1998) suggested that adequate help of individuals coping with mental disorders should involve addressing societal and self-stigma. Kroska and Harkness (2008) explained that self-stigma works in such a way that when an individual is first diagnosed with a mental illness, cultural ideas and stereotypes that have been linked with the mental illness or the mentally ill individuals become personally relevant and promote negative self-feelings. Thereafter, the individual expects others to reject him/her, in turn, triggering defensive behaviors aimed at preventing the rejection.…”
Section: Ssoshmentioning
confidence: 99%
“…Scheff (2010) argued that labelling theory is a social model of mental illness that illustrate that the symptoms of mental illness are recast as violations of social norms. In line with Scheff's arguments, Kroska and Harkness (2008) observed that when an individual is diagnosed with a mental illness, cultural ideas associated with the mentally ill become personally relevant. The societal expectations (from the mentally ill) become a lens through which a patient's behaviour is evaluated.…”
Section: Labelling Theorymentioning
confidence: 66%